Research on Typical Scenarios Based on Fusion Density Peak Value and Entropy Weight Method of Pearson’s Correlation Coefficient - Yuanshang ZHAO; Weifang LIN (Zhongguo dianli)
The volatility and randomness of new energy output make it one of the key problems that need to be solved urgently to obtain typical output scenarios in the planning and operation analysis of new power systems. In this paper, a typical scenario clustering center determination method based on fusion density peak value and entropy weight method of Pearson’s correlation coefficient is proposed. The method first selects the initial clustering center by the density peak value method and then selects the subsequent clustering center based on the entropy weight method. Then, it obtains the final typical scenario by using the backward scenario reduction method. Therefore, this paper takes this method as the core to construct an overall scheme for determining the typical output scenarios of new energy. Finally, this paper uses the daily output scenario of wind power and photovoltaic power in North China in 2021 to carry out an analysis of examples and verification through comparison, which proves the accuracy and effectiveness of the proposed method. The research results will provide more accurate data support for power system planning and operation.